Management of Traditional Dance Preservation at the Indria Tatari Studio, Trenggalek Regency - Ni’am, Salma Aula; Warih Handayaningrum (Solah, 2025)
The preservation of traditional dance is an important part of maintaining the nation’s cultural identity in the midst of modernization. This study aims to analyze preservation efforts, teaching methods, and the role of education in maintaining traditional dance techniques and cultural values among students; identify the presentation of traditional dance movements; and describes the process of creating dance works in a contextual and creative manner at the Indria Tatari Studio, Trenggalek. This research uses a qualitative approach with participatory observation techniques, in-depth interviews, and documentation. The results of the study show that the studio implements gradual learning based on local cultural values, adjustments to dance movements to facilitate students’ understanding without losing philosophical meaning, and the creation of new works such as the Trenggalek Kinasih Dance as a form of traditional cultural actualization. The Tatari Indria Studio has succeeded in forming an adaptive, innovative, and sustainable dance preservation ecosystem through non-formal education.